High thermal conductivity flame retardant organic silicon potting glue for capacitors and preparation method thereof

By adding modified graphene oxide and magnesium aluminum silicate to the silicon potting glue, a three-dimensional crosslinking network structure is formed, and using modified aluminum hydroxide and modified magnesium hydroxide to improve the dispersion of flame retardant and thermal filler, the existing silicon potting glue has been solved, and the low density, high thermal conductivity, high flame retardant and high bonding strength silicone potting glue is achieved.

CN118931485BActive Publication Date: 2025-03-25SICHUAN PROVINCE SCI CITY JIUXIN SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411183869.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-03-25
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

Existing silicon potting adhesives have problems such as high density, low flame retardancy, and poor thermal conductivity, which is difficult to meet the capacitor's demand for low density, high thermal conductivity, high flame retardancy and high bonding strength.

Method used

Using different silicone ratio combinations, the three-dimensional crosslinking network structure is formed by adding modified graphene oxide and magnesium aluminum silicate to improve the adhesive strength, and the dispersion of the flame retardant and the thermal filler is improved by mixing modified aluminum hydroxide and modified magnesium hydroxide.

Benefits of technology

Silicone potting adhesive with low density, high thermal conductivity, good flame retardancy and high bonding strength is realized, which maintains low viscosity and high flowability, and avoids the situation where filler precipitation affects the bonding strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005012976380000201
    Figure BDA0005012976380000201
  • Figure BDA0005012976380000211
    Figure BDA0005012976380000211
Patent Text Reader

Abstract

The present invention discloses a high thermal conductivity flame retardant organic silicon potting glue for capacitors and a preparation method thereof, comprising component A and component B; the component A comprises the following mass fraction components: 80-100 parts of vinyl silicone oil, 20-30 parts of epoxy modified vinyl silicone oil, 50-100 parts of thermal conductive filler, 25-30 parts of magnesium aluminum silicate, 10-15 parts of modified graphene oxide, 0.05-0.5 parts of catalyst, and 10-15 parts of flame retardant; the component B comprises the following mass fraction components: 15-20 parts of vinyl silicone oil, 60-70 parts of vinyl silicone resin, 20-30 parts of flame retardant, 10-15 parts of cross-linking agent, and 0.05-0.5 parts of inhibitor. The present invention adopts different organic silicon ratio combinations, and by adding modified graphene oxide and magnesium aluminum silicate, a three-dimensional cross-linked network structure can be formed, thereby greatly improving the bonding strength, and can improve the dispersibility of flame retardant filler and thermal conductive filler, thereby improving the flame retardancy and thermal conductivity while ensuring its fluidity in use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potting adhesives, and in particular to a highly thermally conductive flame-retardant organic silicon potting adhesive for capacitors and a preparation method thereof. Background Art

[0002] With the continuous development of electronic technology, capacitors are used more and more widely in electronic equipment. In order to protect the stability and safety of capacitors during use, it is usually necessary to use potting glue to encapsulate them. Potting glue is liquid before curing and has fluidity. The viscosity of the glue varies according to the material, performance, and production process of the product. The potting glue can only realize its use value after it is completely cured. After curing, it can play the role of waterproof, moisture-proof, dust-proof, insulation, heat conduction, confidentiality, corrosion resistance, temperature resistance, and shock resistance. There are many types of electronic potting glue. From the type of material, the three most commonly used ones are epoxy resin potting glue, silicone potting glue, and polyurethane potting glue.

[0003] Silicone potting glue has excellent electrical insulation properties, and is ideal for water resistance and UV resistance, so it is a commonly used electronic potting material. However, due to its low molecular polarity, silicone potting glue has poor bonding performance with the substrate after curing, and it is also flammable, so it is necessary to add functional fillers to improve related properties. For example, aluminum hydroxide is added as a flame retardant to improve flame retardancy, and thermal conductive materials are added to improve thermal conductivity. However, adding too little aluminum hydroxide will make it difficult to meet flame retardancy requirements, while adding too much will cause the viscosity of the potting glue to be too low, which is easy to produce precipitation and affect the bonding strength; and the addition of thermal conductive materials will increase the density of the potting glue, making it difficult to meet lightweight requirements.

[0004] Therefore, providing a silicone potting adhesive with low density, high thermal conductivity, good flame retardancy, high bonding strength, low viscosity and good fluidity is a problem that needs to be solved urgently in the prior art.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the existing silicone potting glue has the problems of high density, low flame retardancy, poor thermal conductivity, etc. The purpose is to provide a high thermal conductivity flame retardant organic silicone potting glue for capacitors and a preparation method thereof. By adopting different organic silicone ratio combinations and adding modified graphene oxide and magnesium aluminum silicate, a three-dimensional cross-linked network structure can be formed, thereby greatly improving the bonding strength, and the dispersion of flame retardant fillers and thermal conductive fillers can be improved, thereby improving the flame retardancy and thermal conductivity while ensuring its fluidity in use.

[0007] The present invention is achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a highly thermally conductive flame-retardant silicone potting adhesive for capacitors, comprising component A and component B;

[0009] The component A comprises the following components by mass fraction: 80-100 parts of vinyl silicone oil, 20-30 parts of epoxy-modified vinyl silicone oil, 50-100 parts of thermal conductive filler, 25-30 parts of magnesium aluminum silicate, 10-15 parts of modified graphene oxide, 0.05-0.5 parts of catalyst, and 10-15 parts of flame retardant;

[0010] The component B comprises the following components by mass fraction: 15 to 20 parts of vinyl silicone oil, 60 to 70 parts of vinyl silicone resin, 20 to 30 parts of flame retardant, 10 to 15 parts of cross-linking agent, and 0.05 to 0.5 parts of inhibitor.

[0011] Component A of the present invention includes vinyl silicone oil and epoxy-modified vinyl silicone oil, and component B includes vinyl silicone oil and vinyl silicone resin. The vinyl silicone resin can undergo cross-linking reaction with other components to form a cured product with a cross-linked network structure. This cross-linking reaction enables the silicone potting glue to have better bonding performance and durability, and can maintain stable performance under various environments; epoxy-modified vinyl silicone oil introduces epoxy groups, and the epoxy groups it possesses have higher reactivity in modified epoxy vinyl silicone oils, and can undergo ring-opening reaction with a variety of substances, thereby generating a cross-network structure with vinyl silicone oils and vinyl silicone resins of different molecular weights, and the cross-network structure can avoid the precipitation of free small molecules while improving the curing effect, further improving the bonding performance. In addition, the epoxy-modified vinyl silicone oil used in this application has epoxy end-capping, which can better bond substrates such as metals and glass.

[0012] In a specific embodiment, the modified graphene oxide is coated in the magnesium aluminum silicate, and the specific preparation method is:

[0013] The alkyl orthosilicate, acid and water are uniformly mixed to form a gel, aluminum salt and magnesium salt solution are added dropwise, stirred and mixed uniformly, and ammonia water is added dropwise to obtain magnesium aluminum silicate sol; specifically, 10 parts by weight of methyl orthosilicate, 0.5 parts by weight of 4 mol / L hydrochloric acid and 30 parts by weight of water are mixed, stirred for 15 minutes to form a gel, 25 parts by weight of a solution containing 3 parts by weight of aluminum chloride and 1 part by weight of magnesium chloride are added dropwise, stirred and mixed for 15 minutes, and 10 parts by weight of 25wt% ammonia water are added dropwise to obtain magnesium aluminum silicate sol;

[0014] The modified graphene oxide was added into the magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500° C. for 1 hour, and ball milled for 2 hours to obtain the magnesium aluminum silicate-coated modified graphene oxide.

[0015] In a specific embodiment, the modified graphene oxide is amino-modified using 4,4'-diaminodiphenyl ether; specifically, nano-graphene oxide powder is added to an appropriate amount of N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) is added, and the mixture is stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide.

[0016] The present invention adds magnesium silicate aluminum coated modified graphene oxide to component A. First, graphene oxide is a mesh structure material with nanopores on a two-dimensional base surface. After being amino-modified, it can improve the surface charge of its nanomaterial, making it difficult to flocculate and precipitate, and can be fully dispersed. Then, a layer of magnesium silicate aluminum layer is coated and grown on the outside of the two-dimensional mesh skeleton, which has a large specific surface area and porous structure, and has good oil absorption, so it can enhance the fluidity of the potting glue; and because of its unique mesh structure, the amino-modified graphene oxide undergoes a chemical cross-linking reaction with vinyl silicone oil under the action of a cross-linking agent, and the mesh structure of the graphene oxide is anchored in the cross-linked network structure, and finally forms a three-dimensional cross-network structure, which greatly improves the cross-linking density, enhances the mechanical properties of the potting glue, and improves the thermal conductivity. The amino group of the amino-modified graphene oxide can also react with the epoxy group to form a chemical bond, greatly improving the bonding strength.

[0017] Among them, magnesium aluminum silicate has a large specific surface area and a porous surface. After absorbing oil, it can expand to form a porous gel layer, which cooperates with the network structure of graphene oxide to "fill" the flame retardant and thermal conductive filler into it to hinder the free movement of the filler and prevent coagulation. It can fully improve the flame retardant and thermal conductivity of the potting glue while ensuring the low viscosity and high fluidity, without the situation where the filler precipitation affects the bonding strength.

[0018] In a specific embodiment, the flame retardant in component A is modified aluminum hydroxide with a particle size of 18 to 20 μm;

[0019] The flame retardant in component B includes modified magnesium hydroxide with a particle size of 4 to 5 μm and a non-phosphorus nitrogen flame retardant, and the organic silicon flame retardant is methyl phenyl silicone resin;

[0020] The mass ratio of the modified aluminum hydroxide to the modified magnesium hydroxide is 5:8-10.

[0021] The particle size of aluminum hydroxide powder and magnesium hydroxide powder and the viscosity of the potting compound are normally distributed: the smaller the particle size of the powder, the larger the specific surface area, the larger the contact area between the powder and the potting compound, the more bonding points, the higher the viscosity of the potting compound, and it is not easy to precipitate; conversely, the larger the particle size of the powder, the lower the viscosity of the potting compound, but it is easy to precipitate.

[0022] The present invention adopts a modified aluminum hydroxide with a particle size of 18 to 20 μm and a modified magnesium hydroxide with a particle size of 4 to 5 μm as a flame retardant. The addition of a small amount of modified aluminum hydroxide with a large particle size of 18 to 20 μm can improve the viscosity of the colloid, reduce the viscosity of components A and B before solidification, and enhance their flowability. The addition of a large amount of modified magnesium hydroxide with a small particle size of 4 to 5 μm can significantly improve the problem of particle precipitation. At the same time, combined with the "binding" effect of the network porous structure of magnesium aluminum silicate coated modified graphene oxide on the flame retardant particles, the flame retardant performance can be fully improved while ensuring that the potting glue has the characteristics of low viscosity and not easy to precipitate. The uniformity and flowability are enhanced, thereby extending the mixing time of the two components.

[0023] The flame retardant of the present invention further adds methylphenyl silicone resin, an organic silicon flame retardant, which cooperates with the magnesium-aluminum flame retardant to reduce the impact on the performance of the potting glue and achieve environmentally friendly flame retardancy.

[0024] The flame retardant of mixed particle size and mixed components in the present invention can improve the mutual exclusion problem of low viscosity and sedimentation of potting glue, effectively improve its fusion performance, and when it is used as a filler in epoxy resin potting glue, a low-viscosity and non-precipitation product can be obtained, so that the use time and flow performance of the product are significantly improved.

[0025] In a specific embodiment, modified aluminum hydroxide and modified magnesium hydroxide are modified with dodecyltrimethoxysilane; specifically, 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane with a concentration of 25-35% is added, and the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:1.5-2.5.

[0026] In the present invention, both aluminum hydroxide and magnesium hydroxide are modified by using dodecyltrimethoxysilane, which improves their dispersibility and compatibility in the organic silicon system, thereby effectively improving the mechanical properties and flame retardant properties of the potting glue.

[0027] In a specific embodiment, the preparation process of epoxy-modified vinyl silicone oil is as follows:

[0028] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0029] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, and obtain epoxy-modified vinyl silicone oil by membrane separation and filtration.

[0030] The present invention adopts modified epoxy-modified vinyl silicone oil and vinyl silicone oil and vinyl silicone resin to mix to form an organic silicon system. The cross-linking reaction in the system can make it have a rich cross-linking degree and network structure, and can have better bonding performance and durability.

[0031] In a specific embodiment, the thermal conductive filler includes mesoporous hollow nano-titanium dioxide, modified nano-silicon dioxide and aluminum oxide; the mass ratio of the mesoporous hollow nano-titanium dioxide, modified nano-silicon dioxide and aluminum oxide is 4-5:2.5-4:1-2.

[0032] In a specific embodiment, the preparation process of the mesoporous hollow nano titanium dioxide is as follows: 10 parts by weight of tetrabutyl titanate and 0.2 parts by weight of Span-80 are dissolved in 85 parts by weight of butyl acetate, 55 parts by weight of an aqueous solution containing 0.7 parts by weight of a mesoporous porogen and 0.3 parts by weight of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450°C for 2.5 hours to obtain mesoporous hollow nano titanium dioxide.

[0033] In a specific embodiment, the modified nano-silica is modified using mercaptopropyltrimethoxysilane, specifically: taking silica powder and adding it to a toluene solution, stirring to fully disperse the nano-silica; adding mercaptopropyltrimethoxysilane to the toluene solution dispersed with nano-silica in an oil bath at 75-85°C to react, purifying and drying to obtain the modified nano-silica.

[0034] The present invention adopts a composition of mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide as a thermal conductive filler and adds it to the organic silicon system. Titanium dioxide itself has good thermal conductivity. At the same time, the hollow nanospheres not only reduce the weight of the filler, but also the hollow structure thereof is more conducive to the conduction of heat, so that the thermal conductivity is more uniform, and the total amount of thermal conductive filler added can be reduced, thereby reducing the density of the organic silicon potting glue. The modified nano silicon dioxide adopts mercapto-modified nano silicon dioxide. As an inorganic thermal conductive filler, silicon dioxide is light in weight and can improve the dispersibility of silicon dioxide in the glue after modification, thereby preventing the rapid sedimentation of the filler. Finally, a small amount of aluminum oxide is combined to improve the thermal conductivity. The present invention adopts a composition of mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide as a thermal conductive filler, which is not only conducive to reducing the density of the organic silicon potting glue, but also ensures its thermal conductivity.

[0035] Finally, modified materials such as modified aluminum hydroxide, magnesium hydroxide, modified graphene oxide and modified nano-silica all have electrostatic and large steric hindrance, so they work synergistically with each other, which can further greatly improve the dispersion ability of particles, improve the corresponding performance, and further prevent precipitation.

[0036] In a specific embodiment, the inhibitor may be acetylene cyclohexanol, wherein the vinyl silicone oil may be vinyl-terminated polydimethylsiloxane, and the vinyl silicone resin may be vinyl MQ resin.

[0037] In a specific embodiment, the cross-linking agent is end-side hydrogen-containing silicone oil, and the hydrogen content of the end-side hydrogen-containing silicone oil is 4.5-8.0 mmol / g.

[0038] In a second aspect, the present invention provides a method for preparing a highly thermally conductive flame-retardant organic silicone potting compound for capacitors, comprising the following steps:

[0039] (1) adding vinyl silicone oil, epoxy-modified vinyl silicone oil, and magnesium aluminum silicate-coated modified graphene oxide to a vacuum kneader and kneading them uniformly, then adding a thermal conductive filler and a flame retardant, and kneading them at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; adding a catalyst to the above mixture, and continuing to stir fully to obtain component A;

[0040] (2) kneading vinyl silicone oil, vinyl silicone resin and flame retardant at 100-120° C. under vacuum conditions for 1.5-3 hours; adding a crosslinking agent and an inhibitor to the mixture, and continuing to stir fully to obtain component B;

[0041] (3) Component A and component B are thoroughly stirred and mixed.

[0042] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0043] 1. A highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors and a preparation method thereof provided in an embodiment of the present invention adopts vinyl silicone oil, epoxy-modified vinyl silicone oil and vinyl silicone resin as an organic silicone system. The vinyl silicone resin can undergo a cross-linking reaction with other components to form a cured product with a cross-linked network structure. This cross-linking reaction enables the organic silicone potting adhesive to have better bonding performance and durability, and can maintain stable performance under various environments; epoxy-modified vinyl silicone oil introduces epoxy groups, and the epoxy groups possessed by the epoxy-modified vinyl silicone oil have high reactivity in the modified epoxy vinyl silicone oil, and can undergo a ring-opening reaction with a variety of substances, thereby generating a cross-network structure with vinyl silicone oils and vinyl silicone resins of different molecular weights. While improving the curing effect, the cross-network structure can prevent the precipitation of free small molecules, further improving the bonding performance;

[0044] 2. A highly thermally conductive and flame-retardant organic silicon potting compound for capacitors and a preparation method thereof provided in an embodiment of the present invention. Graphene oxide is a mesh structure material with nanopores on a two-dimensional base surface. After amino modification, the surface charge of the nanomaterial can be improved, making it difficult for itself to flocculate and precipitate, and can be fully dispersed. Then, a layer of magnesium aluminum silicate is coated and grown on the outside of the two-dimensional mesh skeleton, which has a large specific surface area and a porous structure, has good oil absorption, and can enhance the fluidity of the potting compound.

[0045] 3. A highly thermally conductive flame-retardant organic silicone potting compound for capacitors and a preparation method thereof provided in an embodiment of the present invention. Due to its unique network structure, the amino-modified graphene oxide undergoes a chemical cross-linking reaction with vinyl silicone oil or the like under the action of a cross-linking agent, and the graphene oxide with a network structure is anchored in the cross-linked network structure, ultimately forming a three-dimensional cross-network structure, which greatly improves the cross-linking density, thereby enhancing the mechanical properties of the potting compound and improving the thermal conductivity.

[0046] 4. A highly thermally conductive flame-retardant organic silicone potting compound for capacitors and a preparation method thereof provided in an embodiment of the present invention. Magnesium aluminum silicate has a large specific surface area and a porous surface. After absorbing oil, it can expand to form a porous gel layer, which cooperates with the mesh structure of graphene oxide to "fill" the layer with flame retardants and thermally conductive fillers to hinder the free movement of the fillers and prevent coagulation. Thus, the flame retardant and thermal conductivity properties can be fully improved while ensuring the low viscosity and high fluidity of the potting compound, without the situation where the filler precipitation affects the bonding strength;

[0047] 5. A highly thermally conductive flame-retardant organic silicone potting glue for capacitors and a preparation method thereof provided in an embodiment of the present invention adopts a modified aluminum hydroxide with a particle size of 18 to 20 μm and a modified magnesium hydroxide with a particle size of 4 to 5 μm as a flame retardant. The addition of a small amount of modified aluminum hydroxide with a large particle size of 18 to 20 μm can improve the viscosity of the colloid, reduce the viscosity of components A and B before curing, and enhance their flowability. The addition of a large amount of modified magnesium hydroxide with a small particle size of 4 to 5 μm can significantly improve the problem of particle precipitation. At the same time, combined with the "binding" effect of the network porous structure of modified graphene oxide coated with magnesium aluminum silicate on the flame retardant particles, it can fully improve the flame retardant performance while ensuring that the potting glue has the characteristics of low viscosity and not easy to precipitate, and the uniformity and fluidity are enhanced, thereby extending the mixing time of the two components;

[0048] 6. A highly thermally conductive flame-retardant silicone potting compound for capacitors and a preparation method thereof provided in an embodiment of the present invention adopts a composition of mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide as a thermally conductive filler and is added to the silicone system. Titanium dioxide itself has good thermal conductivity. At the same time, the hollow nanospheres not only reduce the weight of the filler, but also the hollow structure is more conducive to the conduction of heat, making the thermal conductivity more uniform, and can reduce the total amount of thermally conductive filler added, thereby reducing the density of the silicone potting compound; the modified nano silicon dioxide adopts mercapto-modified nano silicon dioxide. Silica is light as an inorganic thermally conductive filler. At the same time, the modification can improve the dispersibility of silica in the rubber and prevent the rapid sedimentation of the filler; finally, a small amount of aluminum oxide is combined to improve the thermal conductivity. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0050] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known methods are not specifically described.

[0051] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. Furthermore, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combinations and / or subcombinations.

[0052] Example 1

[0053] The present invention provides a method for preparing a highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors, comprising the following steps:

[0054] (1) Preparation of modified graphene oxide

[0055] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0056] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0057] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0058] 10 parts of modified graphene oxide were added to 25 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0059] (3) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0060] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0061] (4) Preparation of epoxy-modified vinyl silicone oil

[0062] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0063] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0064] (5) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450°C for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0065] (6) Preparation of modified nano-silica

[0066] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0067] (7) Preparation of component A

[0068] 80 parts of vinyl silicone oil, 20 parts of epoxy-modified vinyl silicone oil, and 35 parts of magnesium aluminum silicate-coated modified graphene oxide are added into a vacuum kneader and kneaded evenly, and then 50 parts of thermal conductive filler and 10 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and the mixture is kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.2 parts of platinum catalyst are added to the mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silica and aluminum oxide in the thermal conductive filler is 4:2.5:1;

[0069] (8) Preparation of component B

[0070] 15 parts of vinyl silicone oil, 60 parts of vinyl silicone resin, 16 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 4 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 10 parts of end-side hydrogenated silicone oil and 0.3 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0071] (9) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0072] Example 2

[0073] The present invention provides a method for preparing a highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors, comprising the following steps:

[0074] (1) Preparation of modified graphene oxide

[0075] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0076] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0077] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0078] 15 parts of modified graphene oxide were added to 30 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0079] (3) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0080] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0081] (4) Preparation of epoxy-modified vinyl silicone oil

[0082] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0083] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0084] (5) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450°C for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0085] (6) Preparation of modified nano-silica

[0086] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0087] (7) Preparation of component A

[0088] 100 parts of vinyl silicone oil, 30 parts of epoxy-modified vinyl silicone oil, and 45 parts of magnesium aluminum silicate-coated modified graphene oxide are added to a vacuum kneader and kneaded evenly, and then 100 parts of thermal conductive filler and 15 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.05 to 0.5 parts of platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silica and aluminum oxide in the thermal conductive filler is 5:4:2;

[0089] (8) Preparation of component B

[0090] 20 parts of vinyl silicone oil, 70 parts of vinyl silicone resin, 24 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 6 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 15 parts of end-side hydrogenated silicone oil and 0.5 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0091] (9) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0092] Example 3

[0093] The present invention provides a method for preparing a highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors, comprising the following steps:

[0094] (1) Preparation of modified graphene oxide

[0095] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0096] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0097] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0098] 13 parts of modified graphene oxide were added to 27 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0099] (3) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0100] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0101] (4) Preparation of epoxy-modified vinyl silicone oil

[0102] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0103] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0104] (5) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450°C for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0105] (6) Preparation of modified nano-silica

[0106] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0107] (7) Preparation of component A

[0108] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide are added into a vacuum kneader and kneaded evenly, and then 80 parts of thermal conductive filler and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.1 parts of platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silicon dioxide and aluminum oxide in the thermal conductive filler is 5:3.5:1.5;

[0109] (8) Preparation of component B

[0110] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0111] (9) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0112] Comparative Example 1

[0113] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0114] (1) Preparation of modified graphene oxide

[0115] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0116] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0117] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0118] 13 parts of modified graphene oxide were added to 27 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0119] (3) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0120] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0121] (4) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0122] (5) Preparation of modified nano-silica

[0123] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0124] (6) Preparation of component A

[0125] 115 parts of vinyl silicone oil and 40 parts of magnesium aluminum silicate coated modified graphene oxide are added into a vacuum kneader and kneaded evenly, and then 80 parts of thermal conductive filler and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.1 parts of platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide in the thermal conductive filler is 5:3.5:1.5;

[0126] (7) Preparation of component B

[0127] 85 parts of vinyl silicone oil, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are mixed and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0128] (8) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0129] The difference between this comparative example and Example 3 is that the epoxy-modified vinyl silicone oil and vinyl silicone resin are all replaced by vinyl silicone oil.

[0130] Comparative Example 2

[0131] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0132] (1) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0133] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0134] (2) Preparation of epoxy-modified vinyl silicone oil

[0135] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0136] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0137] (3) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0138] (4) Preparation of modified nano-silica

[0139] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0140] (5) Preparation of component A

[0141] 90 parts of vinyl silicone oil and 25 parts of epoxy-modified vinyl silicone oil are added into a vacuum kneader and kneaded evenly, and then 80 parts of thermal conductive filler and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded for 1.5 to 3 hours at 100 to 120° C. under vacuum conditions; 0.1 parts of platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silicon dioxide and aluminum oxide in the thermal conductive filler is 5:3.5:1.5;

[0142] (6) Preparation of component B

[0143] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0144] (7) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0145] The difference between this comparative example and Example 3 is that magnesium aluminum silicate-coated modified graphene oxide is not added.

[0146] Comparative Example 3

[0147] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0148] (1) Preparation of modified graphene oxide

[0149] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0150] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0151] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0152] 13 parts of modified graphene oxide were added to 27 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0153] (3) Preparation of epoxy-modified vinyl silicone oil

[0154] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0155] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0156] (4) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0157] (5) Preparation of modified nano-silica

[0158] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0159] (6) Preparation of component A

[0160] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide were added into a vacuum kneader and kneaded evenly, and then 80 parts of thermal conductive filler and 13 parts of aluminum hydroxide with a particle size of 25 μm were added, and kneaded for 1.5 to 3 hours at 100 to 120° C. under vacuum conditions; 0.1 parts of platinum catalyst were added to the above mixture, and the mixture was stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silica and aluminum oxide in the thermal conductive filler was 5:3.5:1.5;

[0161] (7) Preparation of component B

[0162] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of magnesium hydroxide with a particle size of 25 μm and 9 parts of methylphenyl silicone resin were kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor were added to the above mixture, and the mixture was stirred thoroughly to obtain component B;

[0163] (8) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0164] The difference between this comparative example and Example 3 is that the aluminum hydroxide and magnesium hydroxide are not modified, and the added particle size is a conventional particle size of 25 μm.

[0165] Comparative Example 4

[0166] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0167] (1) Preparation of modified graphene oxide

[0168] 100 parts of nano-graphene oxide powder were added into N-methylpyrrolidone (NMP) to fully dissolve; then an appropriate amount of 4,4'-diaminodiphenyl ether (ODA) was added, and the mixture was stirred and dispersed under a nitrogen atmosphere, and then filtered, washed, and dried to obtain amino-modified nano-graphene oxide;

[0169] (2) Preparation of magnesium aluminum silicate coated modified graphene oxide:

[0170] 10 parts of methyl orthosilicate, 0.5 parts of 4 mol / L hydrochloric acid and 30 parts of water were mixed and stirred for 15 minutes to form a gel, 25 parts of a solution containing 3 parts of aluminum chloride and 1 part of magnesium chloride were added dropwise, and the mixture was stirred and mixed for 15 minutes, and 10 parts of 25 wt% ammonia water were added dropwise to prepare a magnesium aluminum silicate sol;

[0171] 13 parts of modified graphene oxide were added to 27 parts of magnesium aluminum silicate sol, stirred and mixed for 15 minutes, aged for 2 hours, washed with clean water, calcined at 500°C for 1 hour, and ball milled for 2 hours to obtain magnesium aluminum silicate-coated modified graphene oxide;

[0172] (3) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0173] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0174] (4) Preparation of epoxy-modified vinyl silicone oil

[0175] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0176] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0177] (5) Preparation of component A

[0178] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide are added into a vacuum kneader and kneaded evenly, and then 80 parts of aluminum oxide and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.1 parts of a platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A;

[0179] (6) Preparation of component B

[0180] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0181] (7) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0182] The difference between this comparative example and Example 3 is that the thermal conductive filler is all alumina, and no mesoporous hollow nano titanium dioxide and modified nano silicon dioxide are added.

[0183] Comparative Example 5

[0184] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0185] (1) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0186] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0187] (2) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0188] (3) Preparation of modified nano-silica

[0189] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0190] (4) Preparation of component A

[0191] 115 parts of vinyl silicone oil are added into a vacuum kneader, and then 80 parts of thermal conductive filler and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and the mixture is kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.1 parts of a platinum catalyst are added into the mixture, and the mixture is stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silicon dioxide and aluminum oxide in the thermal conductive filler is 5:3.5:1.5;

[0192] (5) Preparation of component B

[0193] 85 parts of vinyl silicone oil, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are mixed and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0194] (6) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0195] The difference between this comparative example and Example 3 is that the epoxy-modified vinyl silicone oil and vinyl silicone resin are all replaced by vinyl silicone oil, and magnesium aluminum silicate-coated modified graphene oxide is not added.

[0196] Comparative Example 6

[0197] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0198] (1) Preparation of epoxy-modified vinyl silicone oil

[0199] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0200] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0201] (2) The preparation process of mesoporous hollow nano-titanium dioxide is as follows: 10 parts of tetrabutyl titanate and 0.2 parts of Span-80 are dissolved in 85 parts of butyl acetate, and 55 parts of an aqueous solution containing 0.7 parts of a mesoporous porogen and 0.3 parts of Tween-80 are added, stirred and mixed for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano-titanium dioxide;

[0202] (3) Preparation of modified nano-silica

[0203] Add nano-silicon dioxide powder to a toluene solution and stir to fully disperse the nano-silicon dioxide; add mercaptopropyltrimethoxysilane to the toluene solution containing the nano-silicon dioxide under an oil bath temperature of 75-85° C. to react, purify and dry to obtain modified nano-silicon dioxide;

[0204] (4) Preparation of component A

[0205] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide were added into a vacuum kneader and kneaded evenly, and then 80 parts of thermal conductive filler and 13 parts of aluminum hydroxide with a particle size of 25 μm were added, and kneaded for 1.5 to 3 hours at 100 to 120° C. under vacuum conditions; 0.1 parts of platinum catalyst were added to the above mixture, and the mixture was stirred thoroughly to obtain component A; the mass ratio of mesoporous hollow nano-titanium dioxide, modified nano-silica and aluminum oxide in the thermal conductive filler was 5:3.5:1.5;

[0206] (5) Preparation of component B

[0207] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of magnesium hydroxide with a particle size of 25 μm and 9 parts of methylphenyl silicone resin were kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor were added to the above mixture, and the mixture was stirred thoroughly to obtain component B;

[0208] (8) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0209] The difference between this comparative example and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, aluminum hydroxide and magnesium hydroxide are not modified, and the added particle size is a conventional particle size of 25 μm.

[0210] Comparative Example 7

[0211] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0212] (1) Preparation of modified aluminum hydroxide and modified magnesium hydroxide

[0213] 100 parts of aluminum hydroxide or magnesium hydroxide are stirred and dried at 80-100° C. for 2 hours in a mixing device, a xylene solution of dodecyltrimethoxysilane having a concentration of 25-35% is added, the mixture is stirred and reacted at a temperature of 120-140° C. for 0.5-1 hour, filtered and dried to obtain modified aluminum hydroxide and modified magnesium hydroxide; the mass ratio of the aluminum hydroxide or magnesium hydroxide to dodecyltrimethoxysilane is 100:2;

[0214] (2) Preparation of epoxy-modified vinyl silicone oil

[0215] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0216] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0217] (3) Preparation of component A

[0218] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide are added into a vacuum kneader and kneaded evenly, and then 80 parts of aluminum oxide and 13 parts of modified aluminum hydroxide with a particle size of 18 to 20 μm are added, and kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 0.1 parts of a platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A;

[0219] (4) Preparation of component B

[0220] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of modified magnesium hydroxide with a particle size of 4 to 5 μm and 9 parts of methylphenyl silicone resin are kneaded at 100 to 120° C. under vacuum conditions for 1.5 to 3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0221] (5) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0222] The difference between this comparative example and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, the thermal conductive filler is all aluminum oxide, and mesoporous hollow nano titanium dioxide and modified nano silicon dioxide are not added.

[0223] Comparative Example 8

[0224] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0225] (1) Preparation of epoxy-modified vinyl silicone oil

[0226] Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane is added dropwise to a trifluoromethanesulfonic acid aqueous solution having a concentration of 0.0005-0.0015 mol / L, and the hydrolysis reaction is carried out at 60-75° C. for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A;

[0227] Polymerization: Mix the obtained oligomer A with dimethylvinylethoxysilane, add tetraethylammonium hydroxide, react at 80-95°C for 6-10h under nitrogen protection, quickly heat to 170-190°C and keep warm for 1-1.5h to destroy the catalyst, heat to 190-210°C, keep warm for 0.5-1.5h and remove low-boiling substances, separate and filter by membrane to obtain epoxy-modified vinyl silicone oil;

[0228] (2) Preparation of component A

[0229] 90 parts of vinyl silicone oil, 25 parts of epoxy-modified vinyl silicone oil, and 40 parts of magnesium aluminum silicate-coated modified graphene oxide were added into a vacuum kneader and kneaded evenly, and then 80 parts of aluminum oxide and 13 parts of aluminum hydroxide with a particle size of 25 μm were added, and kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 0.1 parts of platinum catalyst were added to the above mixture, and the mixture was stirred continuously to obtain component A;

[0230] (3) Preparation of component B

[0231] 20 parts of vinyl silicone oil, 65 parts of vinyl silicone resin, 21 parts of magnesium hydroxide with a particle size of 25 μm and 9 parts of methylphenyl silicone resin were kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of inhibitor were added to the above mixture, and the mixture was stirred thoroughly to obtain component B;

[0232] (4) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0233] The difference between this comparative example and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, the thermal conductive filler is all aluminum oxide, and mesoporous hollow nano titanium dioxide and modified nano silicon dioxide are not added; aluminum hydroxide and magnesium hydroxide are not modified, and the added particle size is a conventional particle size of 25 μm.

[0234] Comparative Example 9

[0235] The present comparative example provides a method for preparing a silicone potting compound, comprising the following steps:

[0236] (1) Preparation of component A

[0237] 115 parts of vinyl silicone oil are added into a vacuum kneader, and then 80 parts of aluminum oxide and 13 parts of aluminum hydroxide with a particle size of 25 μm are added, and kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 0.1 parts of platinum catalyst are added to the above mixture, and the mixture is stirred thoroughly to obtain component A;

[0238] (2) Preparation of component B

[0239] 85 parts of vinyl silicone oil and 25 parts of magnesium hydroxide with a particle size of 25 μm are kneaded at 100-120° C. under vacuum conditions for 1.5-3 hours; 13 parts of end-side hydrogenated silicone oil and 0.1 parts of an inhibitor are added to the above mixture, and the mixture is stirred thoroughly to obtain component B;

[0240] (3) Component A and component B are thoroughly stirred and mixed, wherein the weight of each component A and component B is the same.

[0241] Performance Testing

[0242] The silicone potting glue prepared in Examples 1-3 and Comparative Examples 1-9 was tested for viscosity according to GB / T10247-2008, thermal conductivity according to GB / T11205-2009, and flame retardancy according to the vertical burning method of GB / T10707-2008; the tensile strength was tested according to GB / T1447-2005; the elongation at break was tested according to GB / T1701-2001; the Shore hardness was tested according to GB / T2411-2008; the bonding strength test method is as follows: the potting glue is coated on the substrate material for bonding, then vacuum degassing and curing, and then a tensile machine is used for shear force test, and the tensile speed is 5mm / min. The sedimentation test method is to take the samples of the potting glue component A and component B respectively, seal them into the sample bottle, and let them stand for 100h at 80°C to observe whether there is precipitation. The test results are shown in Table 1.

[0243] Table 1

[0244]

[0245]

[0246] It can be seen from Table 1 that the difference between Comparative Example 1 and Example 3 is that the epoxy-modified vinyl silicone oil and vinyl silicone resin are all replaced by vinyl silicone oil, so the mechanical properties thereof are somewhat reduced.

[0247] The difference between Comparative Example 2 and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, its viscosity is significantly increased, the thermal conductivity and mechanical properties are greatly reduced, and a small amount of precipitation occurs, indicating that magnesium aluminum silicate coated modified graphene oxide has greatly improved the relevant properties of the potting compound.

[0248] The difference between Comparative Example 3 and Example 3 is that neither aluminum hydroxide nor magnesium hydroxide is modified, and the added particle size is a conventional particle size of 25 μm, and the viscosity thereof does not change significantly. This is because the large particles of aluminum hydroxide ensure its low viscosity. However, since magnesium aluminum silicate-coated modified graphene oxide is added therein, the anti-sedimentation performance of its component A is not significantly affected.

[0249] The difference between Comparative Example 4 and Example 3 is that the thermal conductive filler is all alumina, and no mesoporous hollow nano-titanium dioxide and modified nano-silica are added. Its thermal conductivity is greatly reduced, and the density is significantly increased. There is also a certain loss in related mechanical properties, which shows that mesoporous hollow nano-titanium dioxide and modified nano-silica are beneficial to improving thermal conductivity and reducing the density of the potting compound.

[0250] The difference between Comparative Example 5 and Example 3 is that the epoxy-modified vinyl silicone oil and vinyl silicone resin are all replaced by vinyl silicone oil, and magnesium aluminum silicate-coated modified graphene oxide is not added. It can be seen that the mechanical properties of Comparative Example 5 are significantly reduced, while the viscosity increases and the thermal conductivity also decreases.

[0251] The difference between Comparative Example 6 and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, aluminum hydroxide and magnesium hydroxide are not modified, and the added particle size is a conventional particle size of 25 μm. It can be seen that the viscosity of Comparative Example 6 has not changed significantly. This is because all large particles of aluminum hydroxide ensure its low viscosity. However, since magnesium aluminum silicate coated modified graphene oxide is also reduced, the anti-sedimentation performance of its A component and B component is greatly affected, resulting in more precipitation, and the flame retardant performance is also correspondingly reduced.

[0252] The difference between Comparative Example 7 and Example 3 is that: magnesium aluminum silicate coated modified graphene oxide is not added, the thermal conductive filler is all alumina, and mesoporous hollow nano-titanium dioxide and modified nano-silicon dioxide are not added. The thermal conductivity of Comparative Example 7 drops drastically, which indicates that graphene oxide, mesoporous hollow nano-titanium dioxide and modified nano-silicon dioxide have a significant effect on improving thermal conductivity. At the same time, the density is significantly increased, and the anti-settling performance of component A is also reduced.

[0253] The difference between Comparative Example 8 and Example 3 is that: magnesium aluminum silicate-coated modified graphene oxide is not added, the thermal conductive filler is all alumina, and no mesoporous hollow nano titanium dioxide and modified nano silicon dioxide are added; aluminum hydroxide and magnesium hydroxide are not modified, and the added particle size is a conventional particle size of 25 μm. Compared with Example 3, the viscosity and density of this comparative example are greatly increased, while its thermal conductivity, mechanical properties and flame retardant properties are reduced accordingly. At the same time, more precipitation is produced, and the anti-precipitation performance is poor.

[0254] The potting compound of Comparative Example 9 is relatively close to the existing commercially available ingredients, and only conventional flame retardants and thermal conductive fillers are added thereto. As can be seen from the table, all the properties of the potting compound of Comparative Example 9 are the worst.

[0255] Based on the above conclusions, the organic silicone potting adhesive provided by Examples 1-3 of the present invention has the advantages of low density, low viscosity, good fluidity, high flame retardancy, good thermal conductivity, excellent mechanical properties and not easy to precipitate.

[0256] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A highly thermally conductive flame-retardant silicone potting compound for capacitors, characterized in that: Comprising component A and component B; The component A comprises the following components by mass fraction: 80-100 parts of vinyl silicone oil, 20-30 parts of epoxy-modified vinyl silicone oil, 50-100 parts of thermal conductive filler, 25-30 parts of magnesium aluminum silicate, 10-15 parts of modified graphene oxide, 0.05-0.5 parts of catalyst, and 10-15 parts of flame retardant; The component B comprises the following components by mass fraction: 15-20 parts of vinyl silicone oil, 60-70 parts of vinyl silicone resin, 20-30 parts of flame retardant, 10-15 parts of cross-linking agent, and 0.05-0.5 parts of inhibitor; The modified graphene oxide is modified by amino modification using 4,4'-diaminodiphenyl ether, and the modified graphene oxide is coated in the magnesium aluminum silicate. The specific preparation method is: Alkyl orthosilicate, acid and water are mixed evenly to form a gel, aluminum salt and magnesium salt solution are added dropwise, stirred and mixed evenly, and ammonia water is added dropwise to obtain magnesium aluminum silicate sol; Adding modified graphene oxide to magnesium aluminum silicate sol, stirring and mixing evenly, aging, washing, calcining, and ball milling to obtain magnesium aluminum silicate-coated modified graphene oxide; The flame retardant in the component A is modified aluminum hydroxide with a particle size of 18-20 μm; The flame retardant in component B includes modified magnesium hydroxide with a particle size of 4 to 5 μm and an organic silicon flame retardant; The mass ratio of the modified aluminum hydroxide to the modified magnesium hydroxide is 5:8-10; The preparation process of the epoxy-modified vinyl silicone oil is as follows: (1) Hydrolysis: 3-glycidylpropyl (dimethoxy)methylsilane was added dropwise to a 0.0005-0.0015 mol / L aqueous solution of trifluoromethanesulfonic acid, and the hydrolysis reaction was carried out at 60-75°C for 2-4 hours, followed by distillation, washing, drying, and membrane separation to obtain 3-glycidylpropyl (dimethoxy)methylsilane hydrolysis oligomer A; (2) Polymerization: The obtained oligomer A is mixed with dimethylvinylethoxysilane, tetraethylammonium hydroxide is added, and the mixture is reacted at 80-95°C for 6-10 hours under a nitrogen atmosphere, and the temperature is rapidly raised to 170-190°C and kept for 1-1.5 hours to destroy the catalyst, and the temperature is raised to 190-210°C, kept for 0.5-1.5 hours and low-boiling substances are removed, and the epoxy-modified vinyl silicone oil is obtained by membrane separation and filtration; The thermal conductive filler comprises mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide; the mass ratio of the mesoporous hollow nano titanium dioxide, modified nano silicon dioxide and aluminum oxide is 4-5:2.5-4:1-2.

2. According to claim 1, a highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors, characterized in that: The modified aluminum hydroxide and modified magnesium hydroxide are modified by using dodecyltrimethoxysilane.

3. According to claim 1, a highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors, characterized in that: The cross-linking agent is end-side hydrogen-containing silicone oil.

4. The high thermal conductivity flame retardant organic silicone potting adhesive for capacitors according to claim 1, characterized in that: The preparation process of the mesoporous hollow titanium dioxide nanospheres is as follows: 10 parts by weight of tetrabutyl titanate and 0.2 parts by weight of Span-80 are dissolved in 85 parts by weight of butyl acetate, 55 parts by weight of an aqueous solution containing 0.7 parts by weight of a mesoporous porogen and 0.3 parts by weight of Tween-80 are added, the mixture is stirred for 15 minutes, emulsified at 13500 r / min for 4 minutes, centrifuged at 3000 r / min for 15 minutes, washed with clean water, and calcined at 450° C. for 2.5 hours to obtain mesoporous hollow nano titanium dioxide.

5. The high thermal conductivity flame retardant organic silicone potting adhesive for capacitors according to claim 1, characterized in that: The modified nano-silica is modified by using mercaptopropyltrimethoxysilane, specifically, adding silicon dioxide powder to a toluene solution, stirring to fully disperse the nano-silica; adding mercaptopropyltrimethoxysilane to the toluene solution dispersed with the nano-silica in an oil bath at 75-85° C. to react, purifying, and drying to obtain the modified nano-silica.

6. The method for preparing the highly thermally conductive flame-retardant organic silicone potting adhesive for capacitors according to any one of claims 1 to 5, characterized in that: The steps include: (1) Add vinyl silicone oil, epoxy-modified vinyl silicone oil, and magnesium aluminum silicate-coated modified graphene oxide into a vacuum kneader and knead them evenly, then add thermal conductive filler and flame retardant, and knead them at 100-120° C. under vacuum conditions for 1.5-3 hours; add a catalyst to the above mixture, and continue to stir it thoroughly to obtain component A; (2) Kneading vinyl silicone oil, vinyl silicone resin and flame retardant at 100-120°C under vacuum for 1.5-3h; adding crosslinking agent and inhibitor to the above mixture, and continuing to stir thoroughly to obtain component B; (3) Component A and component B are thoroughly stirred and mixed.

Citation Information

Patent Citations

  • High thermal conductivity nano silicone grease for semiconductor chip heat dissipation

    CN110591365A

  • Lightweight epoxy castable composition and preparation method thereof

    CN116855037A